Influence of phosphorus-deposited fertilizers on the soil phosphate regime - M.A Khayitov; M.I. Mashrabov; N. Esirgapov (International Consortium of Education and Culture Research Studies, 2019)
Under typical soil conditions of Uzbekistan, phosphate-preserving NKFU and PS-agro fertilizers create a favorable phosphate regime in the soil in the vegetable and potato crop rotation system. It has been shown that increasing the fertilizer rate leads to a decrease in the fertilizer efficiency